DISPUTE SETTLEMENT IN DELIMITATION EXCLUSIVE ECONOMIC ZONE THROUGH DIPLOMACY OF STATES: WILL IT SOLVE THE UNDELIMITED? (CASE: INDONESIA AND VIETNAM) - Ninne Zahara Silviani (Journal of Law and Policy Transformation, 2023)
International law has an aim to help international community to ensure the peace and security between states. Whenever a dispute between states arisen in any field of law, there are some choices of dispute settlement, which could be chosen by state entities to solve it, which are diplomatic methods and the adjudicative methods. As mentioned in article 3 point 1(a) of Vienna Convention 1961, the function of diplomatic mission is represent the sending state in the receiving state. The functions are not only in ceremonial attempt. Diplomatic mission also could protest and do inquiries to the receiving states if there are any dispute arisen. Same rule do applied in maritime disputes between Indonesia and Vietnam recently. Indonesian Navy patrol ship under name KRI Tjiptadi 381 was hit by two surveillance vessels owned by the Vietnam Coastguards while pursuing illegal fishing boats on the North Natuna Sea, which is defined as â€œundelimitedâ€ maritime boundaries between Indonesia and Vietnam on Saturday, April 27th 2019. The Indonesian Foreign Ministry then called on the Vietnamese Ambassador as the diplomacy mission of Vietnam in Jakarta to deliver a protest note against a dangerous incident in the North Natuna Sea. This article will discuss about the limitations of diplomatic mission authority in dispute settlement between states, also does the diplomacy settlement could give a better result settling the maritime boundaries dispute.